Effect of thermal annealing on the heat transfer properties of reduced graphite oxide flakes: A nanoscale characterization via scanning thermal microscopy. (November 2016) - Tortello, M.; Colonna, S.; Bernal, M.; Gomez, J.; Pavese, M.; Novara, C.; Giorgis, F.; Maggio, M.; Guerra, G.; Saracco, G.; Gonnelli, R.S.; Fina, A.
Abstract: This paper reports on the thermal properties of reduced graphite oxide (RGO) flakes, studied by means of scanning thermal microscopy (SThM). This technique was demonstrated to allow thermal characterization of the flakes with a spatial resolution of the order of a few tens of nanometers, while recording nanoscale topography at the same time. Several individual RGO flakes were analyzed by SThM, both as obtained after conventional thermal reduction and after a subsequent annealing at 1700 °C. Significant differences in the thermal maps were observed between pristine and annealed flakes, reflecting higher heat dissipation on annealed RGO flakes compared with pristine ones. This result was correlated with the reduction of RGO structure defectiveness. In particular, a substantial reduction of oxidized groups and sp 3 carbons upon annealing was proven by X-ray photoelectron and Raman spectroscopies, while the increase of crystalline order was demonstrated by X-ray diffraction, in terms of higher correlation lengths both along and perpendicular to the graphene planes. Results presented in this paper provide experimental evidence for the qualitative correlation between the defectiveness of graphene-related materials and their thermal conductivity, which is clearly crucial for the exploitation of these materials into thermally conductive nanocomposites.